Nach dem Primitivismus?: Künstlerische Verhandlungen kultureller Differenz in der Bundesrepublik Deutschland, 1960-1990. Eine postkoloniale Relektüre - Wienand, Kea (transcript, 2015)
Art defamed by National Socialism as »degenerate«, referring to supposedly »primitive cultures«, was considered »antifascist« in the Federal Republic of Germany, but whose colonial racisms were reflected? How were these cultural differences negotiated in the art of the FRG from 1960 to 1990?Kea Wienand discusses to what extent artists such as Joseph Beuys, Sigmar Polke, and Ulrike Rosenbach, among others, continued, altered, or criticized primitivism after 1960. She illustrates how beliefs about artistry, sexuality, gender, and history were thematized via images of cultural difference.